The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9ra06528h
|View full text |Cite
|
Sign up to set email alerts
|

A pH-stable positively charged composite nanofiltration membrane with excellent rejection performance

Abstract: A pH-stable positively charged composite nanofiltration (NF) membrane was developed via the interfacial polymerization (IP) between polyethyleneimine (PEI), piperazine (PIP), and cyanuric chloride (CC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Notably, the steric and electronic considerations of amine and isocyanate groups may also impact the rate of polymerization. 52,53 The chemical structures of the monomers evaluated are depicted in Figure 1 and their solubility or miscibility with IL and octane are shown in Table S2. The diamines hexamethylenediamine (HMDA) and 4,4 0 -diaminodiphenylmethane (DAPM) were both soluble in IL and insoluble in octane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the steric and electronic considerations of amine and isocyanate groups may also impact the rate of polymerization. 52,53 The chemical structures of the monomers evaluated are depicted in Figure 1 and their solubility or miscibility with IL and octane are shown in Table S2. The diamines hexamethylenediamine (HMDA) and 4,4 0 -diaminodiphenylmethane (DAPM) were both soluble in IL and insoluble in octane.…”
Section: Resultsmentioning
confidence: 99%
“…Alkyl-amines are more electron-rich than aryl amines of other monomers. 52,53 At higher CO 2 pressures, these amine sites would get saturated and additional capacity would only be due to uptake by the IL. Therefore, the overall gravimetric CO 2 capacity at 760 Torr is smaller for HMDA-HDI than for the agitated [BMIM][PF 6 ] since the capsule mass is about 70 wt % IL.…”
Section: Resultsmentioning
confidence: 99%
“…[ 8–10 ] The topological morphology of the interfacial polymerization substrate is very important for the construction of supramolecular crosslinking polymers. We believe that the combination of interfacial polymerization [ 11,12 ] and electrospinning technology [ 13 ] could be a good universal method for preparing composite nanofiltration membranes, the structures and properties of which can be controlled by means of surface modification, [ 14 ] adjustment of the electrospinning parameters, [ 15 ] and the addition of functional nanoparticles to the spinning solution.…”
Section: Methodsmentioning
confidence: 99%
“…The strong hindrance effect of chloride group in the molecules of CC could protect the amido group from the attack of OH – . Their results showed that the resulting PA layer structure and its separation performance could keep stable in alkali aqueous solution (pH 13) for 30 days [52].…”
Section: High‐performance Nf Membranes For Bio‐separationmentioning
confidence: 99%